2012
DOI: 10.1086/665724
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Aminoglycoside Use and Gentamicin-Resistant Gram-Negative Clinical Isolates in US Academic Medical Centers: Implications for Antimicrobial Stewardship

Abstract: Mean aminoglycoside use declined in this network of US hospitals and was associated with significant and opposite changes in rates of resistance for some organisms and no change for others. At the individual hospital level, antibiograms appear to be an unreliable reflection of antibiotic use, at least for aminoglycosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
2
23
2
Order By: Relevance
“…Consequently, the KDIGO AKI guidelines recommended avoiding AG in patients at risk or with AKI, if possible [9]. We found that AG utilization decreased over the last decade, a finding consistent with results from other multicenter studies [11,35]. …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consequently, the KDIGO AKI guidelines recommended avoiding AG in patients at risk or with AKI, if possible [9]. We found that AG utilization decreased over the last decade, a finding consistent with results from other multicenter studies [11,35]. …”
Section: Discussionsupporting
confidence: 88%
“…In addition, the side effects associated with the prescription of alternative antibiotic agents need to be balanced against those associated with AG. A recent multicenter study reported a sharp decline in AG use over the last decade and a parallel increase in quinolone prescription, which was associated with greater gram-negative bacilli resistance to quinolone [11]. The use of quinolone has also clearly been associated with Clostridium difficile -associated diarrhea [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This downward trend is consistent with national reports of use from 2002 to 2009 showing aminoglycoside use has decrease by 41%. 25 It has Volume 51, October 2016 been suggested that the decreased use in aminoglycosides relates to the availability of other agents with gram-negative activity and superior safety profiles. 26 Corresponding to our decreased aminoglycoside use, we observed increased susceptibility to aminoglycosides with P. aeruginosa, E. coli, and A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…These reports have relied on data from proprietary systems, including single-center studies or multicenter studies that are not nationally representative nor sufficiently large enough to allow projection to the national level [5, 6, 18, 19]. These reports, such as those from the European Union, highlight the importance of considering the source of data [16, 17].…”
Section: Influential Experiencementioning
confidence: 99%